2012
DOI: 10.1021/jp2102463
|View full text |Cite
|
Sign up to set email alerts
|

Charybdotoxin and Margatoxin Acting on the Human Voltage-Gated Potassium Channel hKv1.3 and Its H399N Mutant: An Experimental and Computational Comparison

Abstract: The effect of the pore-blocking peptides charybdotoxin and margatoxin, both scorpion toxins, on currents through human voltage-gated hK(v)1.3 wild-type and hK(v)1.3_H399N mutant potassium channels was characterized by the whole-cell patch clamp technique. In the mutant channels, both toxins hardly blocked current through the channels, although they did prevent C-type inactivation by slowing down the current decay during depolarization. Molecular dynamics simulations suggested that the fast current decay in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…We in fact confirmed this beneficial effect for Apamin (500 nM) and XE991 (10 lM), which reduced the aggregate burden measured in single neurons by microscopy (Appendix Fig S8C ) and decreased the levels of activated caspase 3 (Appendix Fig S8D). Since Charybdotoxin has a broader selectivity (Garcia et al, 1995;Nikouee et al, 2012), it was not investigated further. The anti-synaptotagmin antibody feeding assay, aimed at quantifying pre-synaptic vesicle release (Catanese et al, 2018), confirmed that both Apamin and XE991 increased neuronal firing in treated cultures (Appendix Fig S8E).…”
Section: Resultsmentioning
confidence: 99%
“…We in fact confirmed this beneficial effect for Apamin (500 nM) and XE991 (10 lM), which reduced the aggregate burden measured in single neurons by microscopy (Appendix Fig S8C ) and decreased the levels of activated caspase 3 (Appendix Fig S8D). Since Charybdotoxin has a broader selectivity (Garcia et al, 1995;Nikouee et al, 2012), it was not investigated further. The anti-synaptotagmin antibody feeding assay, aimed at quantifying pre-synaptic vesicle release (Catanese et al, 2018), confirmed that both Apamin and XE991 increased neuronal firing in treated cultures (Appendix Fig S8E).…”
Section: Resultsmentioning
confidence: 99%
“…Recent docking studies predicted that residue K28 in MgTx, which is conserved in α-KTx scorpion toxins, inserts into the pore of the K V 1.3 channel and makes contact with the channel's selectivity filter [50]. In support of this prediction, we found that mutation of MgTx residue K28 to alanine completely abolished the ability of the toxin to inhibit mK V 1.1 and reduced its activity on mK V 1.3 by more than 2000-fold.…”
Section: Discussionmentioning
confidence: 99%
“…In a molecular dynamics study in which His399 within the pore of hKv1.3 was mutated to Asp, the distance between interacting residues of MgTx and Kv1.3 was altered owing to changed electrostatic interactions, which reduced the strength of block (Nikouee et al . ). The Kv1.3 pore and its four voltage sensors are predicted to be 3 nm in length across the membrane (Long et al .…”
Section: Discussionmentioning
confidence: 97%